A natural history study of coagulopathy in a porcine 40% total body surface area burn model reveals the time-dependent significance of functional assays. Issue 8 (December 2022) - McDonough, Matthew M.; Keyloun, John; Orfeo, Thomas; Brummel-Zeidins, Kathleen; Bynum, James A.; Wu, Xiaowu; Darlington, Daniel N.; Shupp, Jeffrey W.; Burmeister, David M.
Abstract: Various studies have reported discordant results on the magnitude and direction of burn-induced coagulopathy (BIC), which has recently been associated with multiple organ dysfunction syndrome (MODS) and death. The increased mechanistic understanding of BIC is due, in part, to novel assays that have expanded the armamentarium beyond traditional tests like PT and aPTT. Still, BIC is a dynamic process, and the progression is difficult to define in the thermally-injured. To this end, we aimed to enhance the understanding of burn-induced coagulation abnormalities by employing functional assessments of platelet aggregation, viscoelastic kinetics, and thrombin generation in an extensive burn model in swine. Anesthetized Yorkshire pigs sustained 40% total body surface area (TBSA) full-thickness contact burns and recovered in metabolic cages. Blood was collected at baseline (BL), as well as 6, 24, and 48 h after injury. A significant effect of burn (P < 0.0001) was seen on platelets, with mild thrombocytopenia apparent at 24 h. While slight decreases in aPTT were not significant, rotational thromboelastometry (ROTEM) analysis revealed hypercoagulation 6 and 24 h after burn by a decreased clotting time. Maximum clot firmness increased after burn, but was not statistically significant until 48 h. Hypercoagulation was not supported by platelet aggregation, as the response to ADP was greatly and persistently diminished, and the response to collagen was unchanged. Endogenous thrombin potential was significantly reduced at 6 and 24 h after burn (P < 0.0001), and also correlated with a number of ROTEM parameters and collagen-induced platelet aggregation. In contrast, PT was not correlated with other measured parameters. Taken together, novel coagulation parameters may be more sensitive than PT in characterizing coagulopathy in the setting of burns. The data presented herein makes initial strides to report the natural history of several of these variables over time in a large animal model of extensive burns, indicating early hypercoagulability followed by hypocoagulation. Future work will elucidate the effects of standard of care. Highlights: PT and aPTT have proven insufficient in identifying BIC. We examined functional clotting parameters in a porcine burn model. Rotational thromboelastometry (ROTEM) indicated acute hypercoagulation. Different agonists of platelet aggregation display varied activity post-burn. Thrombin generation assays reveal later hypocoagulation.